The Wayward Bus Movie Still - Twentieth Century Fox Film Corporation:::Creator::::::::::::
Ernest Horton (Dan Dailey) looking a tad desparate while clinging to the arm of Camille Oaks (Jayne Mansfield). RESTRICTED USE